2001
DOI: 10.1081/al-100001578
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Continuous Wavelet Transform to Resolution of Multicomponent Overlapping Analytical Signals

Abstract: The continuous wavelet transform (CWT) is applied successfully to the resolution of overlapping chromatograms. CWT tends to reinforce the traits of a signal and makes all information more visible due to its redundancy. This is especially true of very subtle information. It is proven by the results that the method is superior to the discrete wavelet transform (DWT) and wavelet packet transform (WPT). CWT has much stronger ability to extract subtle information from seriously overlapping chromatograms, and can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Using exactly the same approach, the WPT resolution and quantitative determination of heavily overlapping chromatograms were also studied. 46 It was found that WPT performs better than the WT approaches. Furthermore, this method was also employed for detection of the number of components in overlapping chromatograms.…”
Section: Baseline/background Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using exactly the same approach, the WPT resolution and quantitative determination of heavily overlapping chromatograms were also studied. 46 It was found that WPT performs better than the WT approaches. Furthermore, this method was also employed for detection of the number of components in overlapping chromatograms.…”
Section: Baseline/background Correctionmentioning
confidence: 99%
“…Using exactly the same approach, the WPT resolution and quantitative determination of heavily overlapping chromatograms were also studied . It was found that WPT performs better than the WT approaches.…”
Section: Applications Of Wavelet Transform In Chemistrymentioning
confidence: 99%
“…In the CWT, a wavelet, , is the analyzing function. This method compares the signal with the shift and dilation of a wavelet [ 35 , 36 , 37 , 38 , 39 , 40 ]. Here, dilation refers to stretched or compressed versions of the wavelet.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, WT can be considered a very efficient tool for data compression [25,26]. Furthermore, since a signal can be decomposed into the components of different frequencies by the wavelet functions of different scales, the resolved signals can be retrieved by WT decomposition from the overlapping signals [27][28][29]. Therefore, WT can be used for resolution enhancement of overlapping signals.…”
Section: Introductionmentioning
confidence: 98%